Análisis De Fragmentación Y Conectividad Para La Cuenca Baja Del Rio Bita, Departamento Del Vichada (2023)
The purpose of this research project is to describe and identify natural areas such as morichal palm swamps, gallery forests, and floodplains that have been affected by the loss of natural vegetation cover due to human activities in the areas belonging to the lower basin of the Bita River in the Department of Vichada